A town like alice eaudiobook - Shute, Nevil (Recorded Books Inc., 2016)
Eight hundred women and children begin a 1,200-mile journey on foot across Japanese-occupied Malaya. At journey's end only 30 will still be alive. This is the story of one woman, of her ordeal, and of how she was saved by the sacrifice of an Australian soldier. It is a story of rare individual courage in the face of certain death, and hope in the face of despair.